Evaluation of Two Ureter Sealing Methods During Radical Nephroureterectomy - Pang, Kun; Chen, Bo; Jiang, Bo; Shi, Zhenduo; Hao, Lin; Zhang, Zhiguo; Zhang, Jianjun; Cai, Longcun; Xia, Tian; Wei, Zhenning; et al. (Urology Journal, 2020)
Purpose: To investigate the safety of electrocoagulation and thulium laser (Tm-laser) sealing methods of distal ureter resection during radical nephroureterectomy (NFU) in a porcine model. Methods: 9 pigs were used in the study: 6 were used to measure the bursting pressure (BP) and 3 were used to measure the highest pressure during NFU. Twelve ureters were to measure BP after being sealed by electrocoagulation or Tm-laser (n = 6, each). Six experimental NFUs were performed in 3 pigs to measure the intraluminal pressure of all procedures. Results: The mean BP in the electrocoagulation group (104.3 ± 25.0 cmH2O) was similar to that of the Tm-laser group (74.8 ± 23.3 cmH2O, P > .05). The peak intraluminal pressure (35.9 ± 7.6 cmH2O) during NFU was significantly lower than the BP (P < .05). Conclusion: The effectiveness of the sealing was confirmed using both electrocoagulation and Tm-laser during NFU.